2013
DOI: 10.1007/s10396-013-0476-x
|View full text |Cite
|
Sign up to set email alerts
|

Microcalcifications in the breast detected by a color Doppler method using twinkling artifacts: some important discussions based on clinical cases and experiments with a new ultrasound modality called multidetector-ultrasonography (MD-US)

Abstract: The twinkling artifact is well known as a color Doppler artifact but it is still an unresolved phenomenon [Rahmouni et al., Radiology 1996;199:269-271 ; Atan et al., Astas Urol Esp 2001;35:396-402; Kamaya et al., AJR 2003;80:215-222]. Many factors affect the appearance of the twinkling artifact, such as the surface roughness of stones creating multiple reflections and a form of intrinsic noise known as clock jitter within the Doppler circuitry of the ultrasound equipment. However, no studies have reported on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…However, due to uncertain mechanisms of TAs, most previous studies have focused only on identifying the effect of US machine imaging parameters (e.g., color gain, electrical noise, or pulse repetition frequency) in large calcifications (a few millimeters) 8–11 . For micron‐size calcifications (e.g., breast MCs), only a small number of studies have been reported since current CDI is limited in consistently presenting TA signals from random distributions 6,12,13 . A few case studies based on conventional CDI were conducted to identify the usefulness of TAs in detecting breast MCs, and the studies discussed the potential for improving breast screening or US‐guided biopsies 12,13 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to uncertain mechanisms of TAs, most previous studies have focused only on identifying the effect of US machine imaging parameters (e.g., color gain, electrical noise, or pulse repetition frequency) in large calcifications (a few millimeters) 8–11 . For micron‐size calcifications (e.g., breast MCs), only a small number of studies have been reported since current CDI is limited in consistently presenting TA signals from random distributions 6,12,13 . A few case studies based on conventional CDI were conducted to identify the usefulness of TAs in detecting breast MCs, and the studies discussed the potential for improving breast screening or US‐guided biopsies 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] For micron-size calcifications (e.g., breast MCs), only a small number of studies have been reported since current CDI is limited in consistently presenting TA signals from random distributions. 6,12,13 A few case studies based on conventional CDI were conducted to identify the usefulness of TAs in detecting breast MCs, and the studies discussed the potential for improving breast screening or US-guided biopsies. 12,13 However, these studies also depend on imaging parameters in commercial US systems and are deficient for a detailed analysis based on the physical mechanism of TAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various studies have suggested that twinkling artifacts on color Doppler and power Doppler imaging can be used effectively to detect calcification (e.g., kidney or urinary stones) 7 , only a few studies have investigated twinkling artifacts in breast microcalcifications 9 , 10 . As breast microcalcifications are small in size (< 1 mm) and are more randomly distributed, current color Doppler imaging cannot consistently present twinkling artifacts 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have investigated various methods to detect calcifications on US, including the use of twinkling artifacts on color Doppler imaging (CDI) and power Doppler imaging 7 , 8 . However, it is difficult to consistently present twinkling artifact signals from randomly distributed micron-size calcifications (e.g., breast microcalcifications) with current CDI and as a result, only a few studies have applied CDI to microcalcifications 9 , 10 . In a previous report, we developed a new microcalcification detection technique using real-time multifocal Doppler twinkling artifact (MDTA) imaging, and reported comparable detection rates for microcalcifications compared to mammography in phantom studies 11 .…”
Section: Introductionmentioning
confidence: 99%